Pengembangan LKPD berbasis Android Untuk Mata Pelajaran Sejarah Kelas XII - FIKRI, ASYRUL (Jurnal Dinamika Sosial Budaya, 2023)
LKPD can help prepare students for school exams or daily tests. The focus of development is on history subjects for class XII (twelve) students. The LKPD contains material and practice questions. The method used in this research is a research and development method using a software development approach in this case is android-based software. The development of android-based LKPD for History Subject Class XII uses the ADDIE model, namely Analysis (analysis), Design (design), Development (development), Implementation (implementation), and Evaluation (evaluation). The data analysis technique used in this research is descriptive analysis, namely by calculating the percentage value of the validation results. The results of the research and discussion are; The assessment from material experts regarding android-based LKPD for Class XII History Subjects obtained an average value of all indicators of 4.20. Based on this assessment, the teaching materials are declared Eligible to use; Assessments from media experts regarding android-based LKPD for Class XII History Subjects obtained an average score of 4.5 in the "Very Eligible" category; and the trial was conducted at SMAN 1 Rumbio Jaya in class XII with 30 students. Students' assessment of the Android-based LKPD obtained an average value of all indicators of 4.0. Based on these data, the Android-based LKPD was declared "Eligible" to use.